Broadening horizons: intestinal microbiota as a novel biomarker and potential treatment for hypertensive disorders of pregnancy - Wang, Min; Zheng, Lianwen; Meng, Yang; Ma, Shuai; Zhao, Donghai; Xu, Ying (Frontiers in Cellular and Infection Microbiology, 2024)
Hypertensive disorders of pregnancy (HDP) are severe complications of pregnancy with high morbidity and are a major cause of increased maternal and infant morbidity and mortality. Currently, there is a lack of effective early diagnostic indicators and safe and effective preventive strategies for HDP in clinical practice, except for monitoring maternal blood pressure levels, the degree of proteinuria, organ involvement and fetal conditions. The intestinal microbiota consists of the gut flora and intestinal environment, which is the largest microecosystem of the human body and participates in material and energy metabolism, gene expression regulation, immunity regulation, and other functions. During pregnancy, due to changes in hormone levels and altered immune function, the intestinal microecological balance is affected, triggering HDP. A dysregulated intestinal microenvironment influences the composition and distribution of the gut flora and changes the intestinal barrier, driving beneficial or harmful bacterial metabolites and inflammatory responses to participate in the development of HDP and promote its malignant development. When the gut flora is dysbiotic and affects blood pressure, supplementation with probiotics and dietary fiber can be used to intervene. In this review, the interaction between the intestinal microbiota and HDP was investigated to explore the feasibility of the gut flora as a novel biomarker of HDP and to provide a new strategy and basis for the prevention and treatment of clinical HDP.